A relação entre neurociência cognitiva e educação no contexto do ensino fundamental I na cidade de Manaus - AM - Oliveira, Karine Carvalho de (Brasil, 2024)
This work aims to present the relationship between cognitive neuroscience and education, seeking to identify the contributions, limits and challenges of cognitive neuroscience to the teaching and learning processes in the early years of Elementary School in the context of the city of Manaus - Am. For this purpose , a Systematic Literature Review was carried out, using the Digital Library of Theses and Dissertations – BDTD and the Catalog of Theses and Dissertations – CAPES as its database. After the research, a documentary analysis was carried out, based on the Municipal Curriculum of Manaus - Am, with the aim of observing the foundations and objectives stipulated for the initial years of Elementary School and their relationships with cognitive neuroscience. The specific objectives are: a) to point out which cognitive processes are most evidenced by research dedicated to the interrelationships between neuroscience and education; b) highlight and analyze the contributions, challenges and limits of cognitive neuroscience to educational processes; c) verify the objectives proposed by the Manaus Municipal Curriculum and their relationship with Cognitive Neuroscience. Among the various authors who support this study, Gardner (2003), Consenza and Guerra (2011), Amaral (2020), Jensen (2011) and Relvas (2011) stand out. The research is qualitative, in which the results point to the need for teachers to understand aspects of Cognitive Neuroscience, so that they can reformulate and strengthen pedagogical practices that actually stimulate students' cognitive processes in a contextualized way, since They are essential for effective and meaningful learning to occur.